Zeolite Integrate with Natural Absorbance to Increase Crop Production - Rashidi, Muhammad Amirul Ashraff; Bahri, Syamsutajri Syamsol; Harun, Zawati; Hussin, Rosniza; Azhar, Faiz Hafeez; Sazali, Norsuhailizah; Hubadillah, Siti Khadijah; Hairom, Nur Hanis Hayati; Jamalludin, Riduan; Rahmawati, Ainun (Emerging Advances in Integrated Technology, 2023)
Mesoporous structure of Zeolites particles with higher micropores able to provide higher surface area that able to increase the efficiency of diffusion mechnism as well as cation exchange capacity (CEC). The uniquness and unreactive properties of zeolites enable to integrate this materials with other potential material to increase the zeolite absorption and CEC performance. Thus, the goal of this work is to study the effect of natural absorbents(chitosan and charcoal) when integrate with zeolite that function as a soil enhancer for the plants growth. Several experiments at different composition of soil, fertilizer, zeolite and absorbance compositions towards  water spinach growth,  pH and soil humidity were measured. The results of the plant growth show that both natural absorbance materials significantly assist the nutrient uptake either from the soil or fertilizer by showing higher plant growth, pH and humidity values as compared to soil mixed with fertilizer only. Integration of these absorbance with zeolite  futher increase the capability of nutrient uptake by giving the highest value of plant growth, pH and humidity values. Detail observation also showed that water spinach grew faster in the sample that had fertilizer added to the zeolite with charcoal as compared to chitosan.